Empowerment of economic potential and status through business capital aids of zakat distribution = Pemerkasaan potensi dan taraf ekonomi melalui agihan zakat bantuan modal perniagaan - Mohamad Halim, Ainin Sofiya; Ishak, Suraiya; Che Omar, Ahmad Raflis; Tahir, Zurinah; Hamdan, Hamdino (Akademi Zakat, Pusat Pungutan Zakat (PPZ-MAIWP), 2025)
Zakat is one of the five pillars of Islam obligated on each Muslim who have fulfilled the specific requirements. Nowadays, zakat distribution has been expanded in the form of business capital aids to develop the potential of asnaf with the ability to work and to enhance their economic level in a sustainable manner. The purpose of the study is to identify and describe the form of value added of Asnaf entrepreneurial programme towards the empowerment of economic potential as well as to measure the economic status of the asnaf entrepreneurs based on the Human Capital Theory. The data collection has been conducted through the distribution of questionnaires involving 40 asnaf entrepreneurs selected through the non-probability sampling, namely the purposive sampling. The data are analysed descriptively by the central tendency values, which are the mean and standard deviation. The study findings shows asnaf entrepreneurial programme value added for asnaf economic potential empowerment has occurred in the form of increased entrepreneurial competencies, availability of business resources and product market opportunities. The level of economic status of the asnaf entrepreneurs shows high achievement scores. The findings prove that zakat distribution in the form of asnaf entrepreneurial programme can reduce poverty among asnaf who possess business capabilities in the long run in line with Human Capital Theory. The implication of the study reiterates that it is worth expanding the scope of the asnaf entrepreneurial programme so that Zakat resources are able to develop the asnaf long-term socio-economic potential. The originality of the study lies in the initiative to examine value added and to measure the increased of economic level derived from the programme empirically